Studi Polimer Biodegradable Untuk Pengemasan Ramah Lingkungan - Maulidia, Jesika; Azizah, Fitriani (Lembaga Publikasi Ilmiah Nusantara, 2025)
The growing awareness of the environmental impacts caused by conventional plastic waste has driven the development of more environmentally friendly alternative materials, one of which is biodegradable polymers. This study aims to explore the potential of biodegradable polymers as sustainable and eco-friendly packaging materials. Biodegradable polymers have the ability to decompose naturally through microbial activity under specific environmental conditions, thereby reducing the accumulation of persistent plastic waste. This study presents a literature review of various types of biodegradable polymers, such as polylactic acid (PLA), polyhydroxyalkanoates (PHA), thermoplastic starch (TPS), and polybutylene succinate (PBS), as well as their applications in the packaging industry. Additionally, the study discusses the challenges faced in implementing biodegradable polymers, including relatively high production costs, limitations in mechanical and thermal properties, and specific degradation conditions. Nevertheless, with ongoing technological advancements and increasing consumer awareness of environmental issues, the use of biodegradable polymers in packaging shows promising prospects. This study concludes that biodegradable polymers represent a potential solution to reduce the environmental impact of conventional plastic use, although further research is required to enhance their performance and production efficiency.